PKM EDUKASI DAN ANTISIPASI PENYEBARAN COVID 19 DALAM MENINGKATKAN PROTOKOL KESEHATAN 4M DI DESA LUWUK GUNUNG SARI SERANG - Sintia Dewi; Dzikri Ramadhan; Anis Nurani; Jaka Wijaya Kusuma; Hamidah Hamidah (STAI Darul Qalam Tangerang, 2022)
Luwuk Village is a village located in Gunungsari district, Serang regency. Where in the village there is very little knowledge to equip themselves to avoid dangerous viruses, where in every house there are still many residents who do not provide masks and equipment to do 5M in the form of preventing the covid 19 virus, therefore we as active students of KKM group 26 universirtas bina bangsa, conduct counseling and socialization to intensify the spread of covid 19 in the village. Currently, we are still facing challenges that require adapting to the Corona Virus Disease 2019 (COVID-19) pandemic situation. Corona Virus Disease-19 is a virus that attacks the respiratory system and can cause mild disorders of the respiratory system, severe lung infections, and even death. Covid-19 can be transmitted from human to human through droplets from patients who sneeze or cough and close contact with sufferers or contact with contaminated surfaces and objects. Covid-19 enters the body through the eyes, nose, and mouth through hands contaminated with the virus. From there, we have held the distribution of masks and hand sanitizers to anticipate the spread of the COVID-19 virus, the community has an important role in breaking the chain of transmission of COVID-19 so as not to cause new sources of transmission / clusters in places where there is movement of people, interaction between people and gathering of many people. People must be able to resume their activities in the COVID-19 pandemic situation by adapting to new habits that are healthier, cleaner, and more obedient, which are implemented by all components in the community and empower all existing resources. The role of the community to be able to break the chain of transmission of COVID-19 (risk of contracting and transmitting) must be carried out by implementing health protocols through individual health protection and public health protection